Critical light instability in CB/DIO processed PBDTTT-EFT: PC71BM organic photovoltaic devices - Pearson, Andrew; Hopkinson, Paul E.; Couderc, Elsa; Domanski, Konrad; Abdi-Jalebi, Mojtaba; Greenham, Neil C. (Organic electronics, 2016)
Organic photovoltaic (OPV) devices often undergo ‘burn-in’ during the early stages of operation, this period describing the relatively rapid drop in power output before stabilising. For normal and inverted PBDTTT-EFT:PC71BM OPVs prepared according to current protocols, we identify a critical and severe light-induced burn-in phase that reduces power conversion efficiency by at least 60% after 24 hours simulated AM1.5 illumination. Such losses result primarily from a reduction in photocurrent, and for inverted devices we correlate this process in-situ with the simultaneous emergence of space-chare effects on the μs timescale. The effects of burn in are also found to reduce the lifetime of photogenerated charge carriers, as determine by in-situ transient photovoltage measurements. To identify the underlying mechanisms of this instability, a range of techniques are employed ex-situ to separate bulk- and electrode-specific degradation processes. We find that whilst the active layer nanostructure and kinetics of free charge generation remain unchanged, partial photobleaching (6% of film O.D.) of PBDTTT-EFT:PC71BM occurs alongside an increase in the ground state bleach decay time of PBDTTT-EFT. We hypothesise that this latter observation may reflect relaxation from excited states on PBDTTT-EFT that do not undergo dissociation into free charges. Owing to the poor lifetime of the reference PBDTTT-EFT:PC71BM OPVs, the fabrication protocol is modified to identify routes for stability enhancement in this initially promising solar cell blend.
Gesehen am 18.06.2020
Im Titel ist 71 in "PC71BM" tiefgestellt
Available online 8 January 2016